PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, DAN ARUS KAS BEBAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI SEKTOR INDUSTRI YANG TERCATAT DI BEI SELAMA PERIODE 2020 – 2023 - Simanungkalit, Beatrix Sabtini; Lumbanbatu, Jessika A C; Siregar, Alfin Dody Pangestu; Mesrawati; Abduh, Arridho (Journal Accounting International Mount Hope, 2025)
Evaluating how much influence company size, debt to equity ratio, profitability level, and free cash flow have on earnings management practices in manufacturing companies classified in the industrial sector and listed on the IDX during the period 2020 to 2023 is the purpose of this research journal. The approach used is quantitative with deductive methods and descriptive in nature. The research information used comes from the annual financial report of a company (secondary data). Multiple linear regression techniques were used to analyze the relationship between the independent variable and the dependent variable. The research results show that each of the independent variables of firm size, debt-equity ratio, profitability, and free cash flow has a significant effect on earnings management with a significance level below 0.05. In addition, the F-test shows that these variables also simultaneously have a significant effect on earnings management, as indicated by the F-test result of 3,643 and a significance of 0.009. These results support the assumption that internal company factors play an important role in earnings management practices, both to maintain the consistency of financial statements and to meet the expectations of stakeholders.